Ambipolar organic field-effect transistors based on N-Unsubstituted thienoisoindigo derivatives. (September 2020) - Yoo, Dongho; Hasegawa, Tsukasa; Kohara, Akihiro; Sugiyama, Haruki; Ashizawa, Minoru; Kawamoto, Tadashi; Masunaga, Hiroyasu; Hikima, Takaaki; Ohta, Noboru; Uekusa, Hidehiro; Matsumoto, Hidetoshi; Mori, Takehiko
Abstract: To investigate a hybrid of isoindigo and thienoisoindigo (TIIG ), a new series of unsymmetrical TIIG analogs, in which one of the outer thiophene rings of TIIG is replaced by benzene (CS ) or pyridine (NS ) are prepared. In addition, the π-skeleton extension effects are studied by examining α-substituted TIIG derivatives with thienyl (Dth-TIIG ), furyl (Dfu-TIIG ), and 1-phenyl-5-pyrazolyl groups (Bis(1-ph-5-py)-TIIG ). These materials exhibit ambipolar transistor properties as expected from the energy levels. Dth-TIIG and Dfu-TIIG show hole mobilities exceeding 0.05 cm 2 V −1 s −1, and electron mobilities about 0.04 cm 2 V −1 s −1, which are close to those of the diphenyl derivative. These molecules are arranged nearly perpendicularly to the substrates in the thin films, and Dth-TIIG has a brickwork-like structure, whereas Dfu-TIIG has uniform columns. CS and Bis(1-ph-5-py)-TIIG have uniform stacking structures, but NS has a dimerized stacking structure due to the slightly bent molecular plane that results from largely unbalanced electron density. Graphical abstract: Image 1 Highlights: A new series of unsymmetrical thienoisoindigo analogs and α-substituted thienoisoindigo derivatives were synthesized. Crystal structures of these materials and transistor performance were systematically investigated. Thienyl substituted thienoisoindigo forms brickwork structures, but it has molecular flipping disorder. This observation suggests possibility of the same kind of disorder in polymers with similar chemical structures.